Bioclimatics in Architecture and Planning Solutions for Medium-Rise Residential Buildings (Journal of Architectural Design, 2023)
This article analyzes the factors influencing the formation of architectural solutions for bioclimatic residential buildings. Based on this analysis, the basic principles of the formation of bioclimatic housing were determined. And also, based on scientific research, a variant of architectural and planning solutions and innovative technologies in the design of modern housing in these conditions are proposed.